2008
DOI: 10.1002/jqs.1179
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy, pollen and 14C dating of Johnston's Gum Hole, a late Quaternary fossil kauri (Agathis australis) site, Northland, New Zealand

Abstract: Johnston's Gum Hole provides a discontinuous pollen record commencing late in Marine Isotope Stage 5 (MIS 5). In combination with other published records from the region, the Aupouri Peninsula is reconstructed to have been continuously forested through much of the last glacial cycle with the oscillation of Agathis-and Nothofagus-dominated forest corresponding to stadials and interstadials, respectively. A northward latitudinal expansion of beech forest to 358 S is demonstrated. Kauri demise at the close of MIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…in our study, glacial Agathis spp. experienced warmer and wetter conditions during the last glacial period compared with modern climates (Elliot et al, 2005;Horrocks et al, 2007;D'Costa et al, 2008). We examined the effects of increasing [CO 2 ] in controlled locations in both study systems; the full Juniperus spp.…”
Section: Box 1: Case Study Testing the Set-point Hypothesis For C I /C Amentioning
confidence: 99%
“…in our study, glacial Agathis spp. experienced warmer and wetter conditions during the last glacial period compared with modern climates (Elliot et al, 2005;Horrocks et al, 2007;D'Costa et al, 2008). We examined the effects of increasing [CO 2 ] in controlled locations in both study systems; the full Juniperus spp.…”
Section: Box 1: Case Study Testing the Set-point Hypothesis For C I /C Amentioning
confidence: 99%
“…This event must be younger than the underlying peats, the minimum age of which is indicated by a radiocarbon age of !50 14 C ka BP (Wk 18540) obtained from an in situ tree stump in palaeosol P1 (Fig. 3) A recent re-evaluation of previously finite ages of wood from Aupouri Peninsula (Hogg et al 2006(Hogg et al , 2007 has shown that much of the wood preserved on Aupouri Peninsula is actually of 'infinite' radiocarbon age and much of the timber is likely to be of Last Interglacial affinity (D'Costa et al 2008). While our radiocarbon age must be regarded as a minimum, the pollen record can be used to refine the age of our sequence by comparison with other Northland pollen records (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…While our radiocarbon age must be regarded as a minimum, the pollen record can be used to refine the age of our sequence by comparison with other Northland pollen records (e.g. Newnham et al 2004;D'Costa et al 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations